Pengembangan Laboratorium Virtual untuk Mata Pelajaran IPAS Materi Gaya Kelas IV SDN Wonokusumo IV/43 Surabaya - Frissenda Septrianur Marinda Karno Putri; Ika Dian Rahmawati (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to: (1) determine ”he validity of the Virtual Laboratory media; (2) Determine the effectiveness of the Virtual Laboratory media; and (3) determine the Attractiveness of the Virtual Laboratory media. This research is a type of R&D (Research and Development) whichh consists of 5 stages, namely analysis, design, Development, implementation, and evaluation. Based on expert assessments, the Average validity percentage obtained Is highly valid. The effectiveness of the virtual Laboratory media is obtained from the student learning mastery results, which Reached 100%. The attractiveness of the virtual laboratory media is obtained from The teacher’s response questionnaire results at 97.5% and the students’ response Questionnaire at 93.75%, placing It in the highly attractive category. Based on the Research results, the virtual laboratory media Is feasible to be used In IPAS learning For 4th-grade students at SDN Wonokusumo IV/43 Surabaya, specifically for Chapter 2 “Force Around Us," with highly vali”, effective, and highly attractive Categories. Many elementary schools face limitations in laboratory facilities and learning media, making it difficult for students to understand abstract science concepts such as force through direct experimentation. Therefore, a virtual laboratory was developed to provide interactive learning experiences and support students in understanding force concepts more effectively. This study aims to: (1) determine the validity of the Virtual Laboratory media; (2) determine the effectiveness of the Virtual Laboratory media; and (3) determine the attractiveness of the Virtual Laboratory media. This research is a type of R&D (Research and Development) which consists of five stages, namely analysis, design, development, implementation, and evaluation.